Effect of green tea extract on cisplatin induced oxidative damage on kidney and testes of rats - LEENA, P; BALARAMAN, R (Ars Pharmaceutica (Internet), 2004)
Green tea extract (Camellia sinensis) was administered orally to rats at the dose levels of 25, 50,100mg/kg to investigate its effect on cisplatin (3mg/kg) induced nephrotoxicity and testicular toxicity. Greentea extract restored the level of creatinine, urea, blood urea nitrogen (BUN) and uric acid in serum ofanimals treated with cisplatin as compared to the animals treated with cisplatin alone. It was furtherfound that administration of green tea extract restored the level of antioxidant enzymes such as, superoxidedismutase (SOD), catalase (CAT) and reduced glutathione (GSH), and membrane bound enzymes likeNa+K+ATPase, Ca2+ATPase and Mg2+ATPase and decreased lipid peroxidation (MDA) in kidney and intestes of animals which were altered after chronic treatment with cisplatin. Thus it can be concluded thatgreen tea extract possesses antioxidant activity and by virtue of this action it can protect the kidney andtestes from cisplatin induced oxidative damage.